2008
DOI: 10.21836/pem20080108
|View full text |Cite
|
Sign up to set email alerts
|

Hysteroscopic removal of uterine cysts in mares II - Follow-up and long term fertility analysis with regard to patho-histological findings

Abstract: SummaryUterine cysts are a common finding during routine transrectal ultrasound examination, often associated with reduced fertility. The aim of this study was to analyse long term fertility of mares after hysteroscopic cyst removal regarding to patho-histological findings. In this study 251 transendoscopic intrauterine surgeries have been performed in 222 barren mares with uterine cysts during the last 11 years. Postoperative endometrial biopsy samples were taken in 83.6% (210/251) of the cases and were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In group 2, the pregnancy rate reached to75% after laser ablation of endometrial cysts. Similar result was obtained before by Kӧllmann et al who reported 74% pregnancy outcome in mares treated from endometrial cysts by intrauterine surgery [35].…”
Section: Discussionsupporting
confidence: 91%
“…In group 2, the pregnancy rate reached to75% after laser ablation of endometrial cysts. Similar result was obtained before by Kӧllmann et al who reported 74% pregnancy outcome in mares treated from endometrial cysts by intrauterine surgery [35].…”
Section: Discussionsupporting
confidence: 91%
“…Details on age, breed, patho-histological results and further breeding results of these mares are given by Köllmann et al (2008).…”
Section: Resultsmentioning
confidence: 99%
“…Compared to other preparation techniques, risk of recurrence is minimized, trauma of the tissue is only superficial and the wound healing is uncomplicated. The results of patho-histological examination of endometrial biopsies and of clinical follow-up with high rates of treated mares conceiving and foaling are presented in the second part of this study by Köllmann et al (2008). …”
Section: Discussionmentioning
confidence: 99%